Strategi Optimalisasi Program Afiliasi TikTok Shop dalam Meningkatkan Penjualan Produk Pilotter - Mochammad Bahauddin Almajidi; Alshaf Pebrianggara (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of digital technology and changes in consumer behavior have driven a shift from offline shopping to e-commerce. One platform utilized in digital marketing is TikTok through its TikTok Shop feature and the TikTok Affiliate program. This community service activity was carried out with Pilotter Gank partners, micro-enterprises in the apparel sector in Gempol District, Pasuruan Regency, who faced challenges in utilizing digital marketing and promotional content. The implementation method included needs identification, planning, training, and mentoring in optimizing TikTok Affiliate. The activity focused on creating video-based promotional content and utilizing the affiliate feature. Results showed an increase in partner capacity, indicated by the ability to produce 5-10 promotional content pieces and improved content performance with views exceeding 1,000. Furthermore, sales increased from 688 products to 12,745, with revenue increasing from Rp95,245,641 to Rp1,518,211,355. Thus, the TikTok Shop affiliate program proved to be an effective and efficient digital marketing strategy in increasing Pilotter Gank product sales.